THE CHALLENGE AND INNOVATION OF MADRASAH LEARNING AS AN ISLAMIC EDUCATION INSTITUTION IN THE ERA OF DIGITAL TECHNOLOGY: Tantangan dan inovasi Pembelajaran Madrasah Sebagai Lembaga Pendidikan Islam Di Era Teknologi Digital - Nadlif, Ainun (Academic Journal Research, 2023)
The purpose of this research is to answer the causes of the problems felt by Madrasahs as Islamic educational institutions that feel the sweetness of the challenges of education from time to time. Madrasahs have always been an Islamic educational institution that occupies a position that is not the main or domesticated in the world of national education. Always imaging Madrasah is an educational institution that is organized as it is, the important thing is that there is a Madrasah, there are teachers who teach in class and learning activities take place in accordance with policies regulated by National Education. Another crucial problem is the readiness of Madrasahs to face changes in the era of digital information technology, which is currently something that is symptomatic in all aspects of life. Madrasahs are Islamic educational institutions that are responsible for producing future generations for the Nation and State.  The current situation must really be responded actively, positively by Madrasahs in order to be able to symbiosis with the challenges that occur. This type of research is literary research, which is reference-based research that provides scientific information about the existence of Madrasahs and their challenges in the present and future. Data collection uses books, ebooks, journal articles, and others similar.